Implikasi Pemahaman Makna Mutu dan Audit Mutu Dalam Penyelenggaraan Pendidikan Kristen Yang Berkualitas - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2023)
The implementation of high quality and professional Christian education cannot be compromised or measured anymore, in other words it has become an obligation, a necessity and a fixed price. It is a must for all educational institutions in Indonesia, including Christian education. Understanding and applying the meaning of quality and quality audit in the implementation of Christian education is very important for all parties involved. This research was conducted by library research. The results of this study produce very important implications for the life and professionalism and accountability of quality Christian education governance, namely: First, the implementation of Christian education must be managed in a quality manner. Second, setting targets for periodic audit programs. Third, train competent quality auditors. Fourth, strategically monitor and measure the quality level of satisfaction. Fifth, Making product and service quality a competitive strategy. Sixth, prime service is an important key in christian education management.